THE CONCEPT AND ESSENCE OF THE LAW "ON THE PUBLIC CIVIL SERVICE" AND ITS SIGNIFICANCE IN LABOR RELATIONS - Rejapova Dilafruz Akramovna (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
This article describes and construes the addoption of the Law "On State Civil Service" by the President and the Law on recruitment to the State Civil Service, rights and obligations in labor relations, personnel rotation, their working hours and specific features of State Civil Service, business trips as well as the social protection of the civil servant which is carried out by the government